Intestinal Parasitic Infection among School Age Children - Bhandari, N; Kausaph, V; Neupane, G P (Journal of Nepal Health Research Council, 2011)
Background: World Health Organization estimates one-fourth of world’s population harbors one or more intestinal parasites. Intestinal parasites are among the most common infections of school age children causing-nutritional deficiency, chronic dysentery, rectal prolapse, poor weight gains, retarded growth and mental retardation. Methods: The stool samples were collected from school going children and examined for intestinal parasite by normal saline wet mount, formalin ether sedimentation technique was performed for the concentration. Results: Among 360 school age students, the prevalence of intestinal parasite was found 40%. Among the positive cases of which 60% were female. It was observed that the rate of parasitic infection among positive cases, Newar was 35(36.84%), Chettri 31(32.97%) and Brahmin and others 29(33.72%) respectively. The study detects an association between intestinal parasitic infection and drinking tape water. Conclusions: The findings of this study showed that intestinal parasitic infections remain prevalent in the study area. The high prevalence of parasitic infections seems directly related to the unhygienic living conditions. This strongly indicates a need for intervention measures likely-to take up sustained health education, provision of safe drinking water and improvement in environmental sanitation and to provide the school student with health education. Keywords: Ascaris lumbricoides, Ancylostoma duodenale, Giardia lamblia, intestinal parasitic infection, Trichuris trichuria.